The role of progesterone and the progesterone receptor in cancer. Issue 3 (4th May 2017) - Check, Jerome H
ABSTRACT: Introduction : There is an abundance of accumulating data strongly suggesting there is a key role for the progesterone receptor in the molecular events effecting the growth or containment of a variety of cancers. This knowledge should lead to novel new strategies to combat various cancers, including drugs classified as progesterone receptor modulators or monoclonal antibodies against some of the key proteins needed for cancer proliferation by suppressing immune surveillance. Areas covered : The role of the classic nuclear receptor and molecular events needed for proliferation are reviewed including cancers of the breast, endometrium, prostate, thyroid, and leiomyomas and leiomyosarcoma. The potential role of non-genomic membrane progesterone receptors is reviewed. The prognostic role of the presence of progesterone receptors is also discussed. Over 1000 research publications were read after conducting a PubMed search. Expert commentary : Discussion is made about a unique immunomodulatory protein called the progesterone induced blocking factor (PIBF). The role of this protein, that is unique to rapidly growing cells, may hold a key to how the cancer cells escape immune surveillance. Thus, techniques to suppress the intracytoplasmic isoforms of PIBF may play a significant role in the fight against all cancers, not just the ones with the classic nuclear progesterone receptors.